Microcytic hypochromic Anemia is a risk factor for postoperative HAEC: A retrospective study - Huang, Yuanyuan; Ren, Hongxia (Frontiers in Surgery, 2023)
Hirschsprung-associated Enterocolitis(HAEC)is a common and life-threatening complication of Hirschsprung disease(HSCR) ,that can occur both before and after surgery.Our aim is to identify the risk factors associated with the development of HAEC.